ANALISA PENGARUH STORE CORPORATE IMAGE DAN CUSTOMER SATISFACTION TERHADAP STORE FIRM PERFORMANCE PADA USAHA RETAIL BOUTIQUE DI SURABAYA - Selan, Alvionita Stifanny (Business Accounting Review, 2015)
The purpose of this study was to examine the affect of store corporate image on store firmâs performance through customerâs satisfaction as the intervening variable on retail boutique in Surabaya. Sample of this study was 40 retail stores in fashion industry in Surabaya. The data were collected by distributing questionnaires to the management and constumers of each retail. This study used path modeling analysis technique with PLS. The results showed that there were positive and significant affect of store corporate image on customerâs satisfaction, positive and significant affect of customerâs satisfaction on store firm performance, and also positive and significant affect of store corporate image on store firmâs performance on retail boutique in Surabaya.